2021
DOI: 10.3390/ma14040791
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ti and Cu Addition on Inclusion Modification and Corrosion Behavior in Simulated Coarse-Grained Heat-Affected Zone of Low-Alloy Steels

Abstract: In this paper, the effects of Ti and Cu addition on inclusion modification and corrosion behavior in the simulated coarse-grained heat-affected zone (CGHAZ) of low-alloy steels were investigated by using in-situ scanning vibration electrode technique (SVET), scanning electron microscope/energy-dispersive X-ray spectroscopy (SEM/EDS), and electrochemical workstation. The results demonstrated that the complex inclusions formed in Cu-bearing steel were (Ti, Al, Mn)-Ox-MnS, which was similar to that in base steel.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…AF is staggered, interlocked and formed on non-metallic inclusions. The M/A constituent is a mixture of untempered martensite embedded in carbon-enriched retained austenite [ 4 , 5 ]. As a result, the CGHAZ is considered to be the weakest area in the welded joint [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AF is staggered, interlocked and formed on non-metallic inclusions. The M/A constituent is a mixture of untempered martensite embedded in carbon-enriched retained austenite [ 4 , 5 ]. As a result, the CGHAZ is considered to be the weakest area in the welded joint [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the types of non-metallic inclusions—such as Al 2 O 3 , MnS, ZrO 2 , CaO and Al 2 MgO 4 —introduced in steels depend on the specific deoxidation techniques [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Inclusions in the steels are often considered as defects that can preferably be attacked by chloride ions in the marine environment, which induce pitting corrosion [ 4 , 16 , 17 ] that has a detrimental impact on application performance [ 18 , 19 , 20 , 21 , 22 , 23 ]. Numerous studies have been conducted on the local corrosion caused by inclusions in HSLA steels.…”
Section: Introductionmentioning
confidence: 99%
“…However, some researchers believe it is related to anodic polarization. Studies have shown that only 0.1 wt.% of Cu can significantly improve the atmospheric corrosion resistance of steel [ 16 , 17 , 18 , 19 ]. To date, few studies have reported the effect of Cu on the formation of reversed austenite in super martensitic stainless steel.…”
Section: Introductionmentioning
confidence: 99%
“…Park et al [ 10 ] examined the hydrogen-induced cracking caused by galvanic corrosion of an ASTM A516-65 steel weld in a wet sour environment using a combination of a standard immersion corrosion test, electrochemical analyses and morphological observation of the corrosion damage. Wang et al [ 11 ] investigated the effects of Ti and Cu addition on inclusion modification and corrosion behavior in the simulated coarse-grained heat-affected zone of low-alloy steels by using an in situ scanning vibration electrode technique, a scanning electron microscope/energy-dispersive X-ray spectroscopy and an electrochemical workstation. The corrosion feature of Q235B steel in desulfurization solution is studied by Gong et al [ 12 ].…”
mentioning
confidence: 99%